Systematics of the Culex coronator complex (Diptera: Culicidae): Morphological and molecular assessment - Laurito, Magdalena (2017)
The Culex coronator complex of the mosquito subgenus Culex includes five currently recognized species: Cx. camposi, Cx. coronator, Cx. ousqua, Cx. usquatissimus and Cx. usquatus. Because of the confusing taxonomic history of the complex, we aimed to clarify the specific status of these nominal forms based on an examination of holotypes and lectotypes and molecular data from other specimens. Critical assessment of published descriptions and study of type specimens revealed that the known distributions of the five species overlap considerably and exhibit biotic sympatry in some areas. Sequences from the COI barcode region and complete mitochondrial genomes were used to assess the relationships and degree of genetic divergence of the species and two newly discovered morphological forms, Cx. coronator Forms 1 and 2. Genetic distances in the COI dataset varied from 0.00 to 2.67%, with the largest relative divergence being 4.41 between specimens of Cx. coronator and Cx. coronator Form 1. Bayesian Poisson tree process analysis of the COI barcode region also failed to provide support for the nominal species. Evidence from the morphological and molecular data thus leads us to conclude (at least provisionally) that the Cx. coronator complex is a single polymorphic species. The forms constitute a monophyletic group but there is no support for the specific status of the five nominal forms.